The heritability of circulating testosterone, oestradiol, oestrone and sex hormone binding globulin concentrations in men: the Framingham Heart Study. (27th June 2013) - Travison, T. G.; Zhuang, W. V.; Lunetta, K. L.; Karasik, D.; Bhasin, S.; Kiel, D. P.; Coviello, A. D.; Murabito, J. M.
Summary Objective Circulating testosterone, oestradiol and oestrone concentrations vary considerably between men. Although a substantial proportion of this variation may be attributed to morbidity and behavioural factors, these cannot account for its entirety, suggesting genetic inheritance as a potential additional determinant. The analysis described here was intended to estimate the heritability of male circulating total testosterone (TT), calculated free testosterone (cFT), oestrone (E1), oestradiol (E2) and sex hormone binding globulin (SHBG), along with the genetic correlation between these factors. Design Cross‐sectional, observational analysis of data from male members of the Offspring and Generation 3 cohorts of the Framingham Heart Study. Data were collected in the years 1998–2005. Participants A total of 3367 community‐dwelling men contributed to the analysis, including 1066 father/son and 1284 brother pairs among other family relationships. Measurements Levels of serum sex steroids (TT, E1 and E2) were measured by liquid chromatography–tandem mass spectrometry, SHBG by immunofluorometric assay and cFT by mass action equation. Heritability was obtained using variance components analysis with adjustment for covariates including age, diabetes mellitus, body mass index and smoking status. Results Age‐adjusted heritability estimates were 0·19, 0·40, 0·40, 0·30 and 0·41 for cFT, TT, E1, E2 and SHBG, respectively. Adjustment for covariates did not substantially attenuate these estimates; SHBG‐adjusted TT results were similar to those obtained for cFT. Genetic correlation coefficients (ρG) indicated substantial genetic association between TT and cFT (ρG = 0·68), between TT and SHBG (pG = 0·87), between E1 and E2 (ρG = 0·46) and between TT and E2 (ρG = 0·48). Conclusion Circulating testosterone, oestradiol and oestrone concentrations exhibit substantial heritability in adult men. Significant genetic association between testosterone and oestrogen levels suggests shared genetic pathways.